Phototoxic liposomes coupled to an antibody that alone cannot modulate its cell-surface antigen kill selected target cells. - Yemul, S; Berger, C; Katz, M; Estabrook, A; Edelson, R; Bayley, H (Springer-Verlag, 1990)
Molecules such as antibodies that bind to cell surfaces can be used to deliver cytotoxic drugs to selected cells. To be effective the drug must usually be taken into the cells by endocytosis. In this study a T-cell line (CCRF-CEM) was effectively killed by liposomes carrying a photosensitizer and bearing the antibody OKT4 (anti-CD4). The unconjugated antibody does not induce antigenic modulation in the target cells, an indication of the absence of endocytosis, and would therefore not normally have been selected as an agent for drug delivery. It cannot, however, be concluded with certainty that the conjugates act at the cell surface and several alternative explanations of their efficacy are offered.